STRATEGI KEBIJAKAN PEMBENTUKAN BRIN COORPORATE UNIVERSITY - AYURISYA DOMINATA (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2021)
The excellence of educational and training institutions is one of the keys to succeed in achieving the performance of research and innovation bodies such as the National Research and Innovation Agency (BRIN). Moreover, institutions that have strategic goals to encourage increased productivity of inventions and innovations of researchers to strengthen competitive and sustainable economic transformation in Indonesia. However, there are a number of obstacles to achieving these goals, for example the traditional education system and the old approach, the unavailability of a link and match between the education and training program and the organization's vision and mission, as well as the business as usual training program and the complexity of the bureaucracy, resulting in the output of education and training institutions, did not reach the maximum target. One of the strategies adopted by many countries in the world and also by a number of ministries/agencies in Indonesia to deal with this is to transform their educational and training institutions into a Corporate University (Corpu). Corporate University, is a new form of training institution that is more modern and dynamic, replacing the previous learning method which was only limited to training and development, becoming learning and development. This research aims to identify and analyze policy strategies that can be carried out by BRIN in establishing a Corporate University. This research uses qualitative methods, with data collection techniques through observation, interviews, and documentation studies. The results of the study conclude several important steps to build BRIN Corporate University (CU). First, it is necessary to draft a policy formulation for the establishment of BRIN Corporate University (CU), as well as conduct advocacy so that this policy gets full support from the highest leadership of the institution. Second, it is necessary to establish a CU 'governing body' by involving experts from certain relevant fields/sciences. Third, identify and formulate the vision and mission of BRIN Corporate University. Fourth, determine funding system policies, stakeholder roles, and learning models. Fifth, make a formal policy regarding the use of technology and adequate learning media. Sixth, Ensure the involvement of every element of the institution or organization. Seventh, consider the possibility of establishing partnerships with universities. Eighth, the formation of a cross-functional team from business lines that can be used to launch BRIN Corporate University. ABSTRAKLembaga pendidikan dan pelatihan yang berkualitas merupakan salah satu kunci keberhasilan pencapaian kinerja badan riset dan inovasi seperti Badan Riset dan Inovasi Nasional (BRIN) yang memiliki target mendorong tumbuhnya produktivitas aktivitas riset sehingga dapat mendorong daya saing bangsa. Namun, kendala sistem pendidikan lembaga diklat yang masih tradisional dan menggunakan pendekatan lama, belum adanya link and match antara program diklat dengan visi misi organisasi, juga program diklat yang bersifat business as usual dan sangat birokratis, menyebabkan banyak ouput lembaga pendidikan dan pelatihan ASN di Indonesia saat ini belum mampu mencapai target lembaganya. Salah satu strategi yang dilakukan banyak negara di dunia dan juga mulai dilakukan oleh sejumlah kementerian/lembaga di Indonesia untuk menyiasati hal ini adalah melakukan transformasi lembaga pendidikan dan pelatihan mereka menjadi Coorporate University (Corpu). Corporate University, adalah bentuk baru dari lembaga diklat yang lebih modern dan dinamis, menggantikan metode pembelajaran sebelumnya yang hanya sebatas training and development, menjadi learning and development. Riset ini bertujuan melakukan identifikasi dan analisis tentang strategi kebijakan yang dapat dilakukan oleh BRIN dalam membentuk Corporate University. Riset ini menggunakan metode deskriptif kualitatif, dimana peneliti melakukan pengumpulan data dengan teknik observasi, studi literatur, dan wawancara. Hasil penelitian menyimpulkan beberapa langkah penting untuk membangun BRIN Corporate University (CU). Pertama, menyusun rancangan formulasi kebijakan pembentukan BRIN Corporate University (CU), sekaligus melakukan advokasi sehingga kebijakan ini mendapat dukungan penuh dari pimpinan tertinggi lembaga juga stakeholder terkait. Kedua, melakukan pembentukan 'governing body' CU dengan melibatkan para ahli dari bidang/ilmu tertentu yang relevan. Ketiga, mengidentifikasi dan merumuskan visi dan misi BRIN Corporate University. Keempat, merumuskan kebijakan terkait sistem pendanaan dan model pembelajaran. Kelima, membuat kebijakan formal tentang pemanfaatan teknologi dan media pembelajaran yang memadai. Keenam, memastikan keterlibatan penuh seluruh unsur lembaga. Ketujuh, mempertimbangkan kemungkinan membangun kemitraan dengan perguruan tinggi. Kedelapan, pembentukan tim lintas fungsi dari lini bisnis yang dapat digunakan untuk meluncurkan BRIN Corporate University.